TEKTONIK GEOMORFOLOGI SESAR-SESAR YANG DIDUGA AKTIF DI DAERAH HILIR SUNGAI BONE, GORONTALO - Masulili, F.; Djaya, A. E. P.; Walukow, J. L.; Bolung, R. Y.; Gafur, N. A. (LPPM Universitas PRISMA, 2023)
The downstream area of ​​the Bone River is the center of government, economy and settlement in Gorontalo Province. This area is located in the North Arm of Sulawesi which is tectonically and seismically active and is directly influenced by the Sangihe Tunjaman in the eastern partand Tunjaman Sulawesi in the north. However, information regarding active faults in disaster mitigation efforts is still very minimal. For the first time, we have mapped active faults around the lower reaches of the Bone River based on morphometric interpretation protection index red relief image map (MPI-RRIM). The Pancuran normal fault and the Bondawuna normal fault on the south side show this evidence of Quaternary activity, compared to the normal Lombongo fault on the north side. Based on the empirical relationship between moment magnitude and length of surface cracks, these faults have the potential to produce earthquakes of 6.3 6.7 Mw. Besides Therefore, our research found that the flood disasters that often hit this area are not only influenced by climate and urbanization, but also controlled by tectonic activity. Understanding active cesarean delivery is very important in improving education community related to disasters, and also as basic information in regional development planning.